Peak-to-Average Power Ratio Reduction Method for OFDM Signal by Permutation of Subcarriers - Pornpawit Boonsrimuang; Kanchana Limwattanacha; Pisit Boonsrimuang; Hideo Kobayashi (My University, 1970)
Many PAPR reduction methods for OFDM time domain signal have been proposed up to today, all of which can be classified into two kinds of methods as the distortion and distortion-less methods. The most of distortion-less methods show better PAPR performance without degradation of BER performance. However the distortion-less methods are usually required to control the transmission data information so as to minimize the PAPR performance at the transmitter. From this fact, the distortion-less methods are required to inform the controlled information as the side information to the receiver for the correct demodulation of data information. The side information is usually informed to the receiver with the higher signal quality by using the separate channel or the embedded in the data information which would lead the degradation of transmission efficiency and the increase of hardware complexity of transmitter and receiver.
This paper proposes a novel distortion-less PAPR reduction method which employs the permutation of subcarriers in the frequency domain. The feature of proposed method is to achieve the better PAPR performance with a very few embedded side information for the correct demodulation of data information at the receiver. This paper presents various computer simulation results to verify the effectiveness of proposed method as comparing with the conventional OFDM method in the non-linear channel.
Keywords: Distortion (music); SIGNAL (programming language); null